2011
DOI: 10.4067/s0718-95162011000100003
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMAL PARAMETERS FORT In Vitro DEVELOPMENT OF THE HYDROCARBONOCLASTIC MICROORGANISM Proteus sp

Abstract: In México, there are extensive areas polluted by oil spills. Currently, bioremediation technologies have been developed, using microorganisms to clean up oil sites. In this study, we evaluated the development of a hydrocarbonoclastic bacterial strain, using a completely randomized 3x3x4 factor arrangement: three temperatures, three pH, and four nutrients. We collected samples of soil contaminated with 3.45 x 10 5 mg kg -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
5
0
6
Order By: Relevance
“…strain which could be useful as a sole degrader of oil hydrocarbons in soil was presented by Hernandez-Rivera et al . [57]. The strain may be presumed to belong to P. vulgaris group due to indole production and maltose fermentation abilities observed by the authors (see Table 1).…”
Section: Proteus In Bioremediation and Plant Growth Promotionmentioning
confidence: 99%
“…strain which could be useful as a sole degrader of oil hydrocarbons in soil was presented by Hernandez-Rivera et al . [57]. The strain may be presumed to belong to P. vulgaris group due to indole production and maltose fermentation abilities observed by the authors (see Table 1).…”
Section: Proteus In Bioremediation and Plant Growth Promotionmentioning
confidence: 99%
“…can degrade chlorpyrifos up to 150 mg/L within 120 hours. A study by Hernández et al (2011) showed that Proteus sp. can degrade chlorpyrifos up to 83.60% within 72 hours of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorpyrifos compound is a hydrocarbon compound that is used as a poison for insect pests. According to Hernández et al (2011), there are types of bacteria that are able to utilize hydrocarbon compounds as a source of metabolic energy in their bodies, and these bacteria are called hydrocarbonoclastic bacteria. According to Gray et al (2013), bacteria that can utilize hydrocarbon compounds have a special responsibility to toxic compounds such as chlorine and phosphate by releasing catalase and peroxidase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the Penicillium sp. degraded crude oil, using it as its sole source of carbon and energy [16,23,25,26,28,[64][65][66], or oil derivates with the same purpose [9,25,29,31,63]. This can be attributed to the fact that Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%